TEACHING SPEAKING USING FISHBOWL DISCUSSION STRATEGY AT THE SEVENTH GRADE OF SMP NEGERI I GALIS - Bambang Sutrisno (Universitas Madura, 2018)
Many factors can cause the students speaking namely the student interesting in teaching english strategy. As we have known that many strategies can be applied in teaching speaking including fishbowl discussion strategy and the research findings say that fishbowl discussion strategy is effective and creative to use in teaching sepaking. Because of that, the researcher want to observe teaching speaking using fishbowl discussion strategy at the seventh grade of SMP Negeri I Galis Pamekasan. The objective of the study are to describe how teacher applies fishbowl discussion strategy in teaching speaking at the seventh grade students of SMPN 1 Galis Pamekasan. To find out the student’s respond on teaching speaking using fishbowl discussion strategy at the seventh grade of SMPN 1 Galis Pamekasan. In research design of this study used descriptive qualitative research. The object is students of the seventh Grade of SMP Negeri I Galis Pamekasan. The researcher conduct this research two times. The instruments used to got the data were: observation, interview and documentation. Observation was applied in order to know the teacher applies fishbowl discussion strategy in teaching speaking at the seventh grade of SMP Negeri I Galis Pamekasan and the activity in the class. Interview were conducted to know the teacher’s difficulties in teaching speaking English and the students respond on teaching speaking using fishbowl discussion strategy at the sevnth grade of SMP Negeri I Galis Pamekasan. The result showed that teaching speaking using fishbowl discussion strategy at the seventh grade of SMP Negeri I Galis Pamekasan gave the positive responses because teaching speaking using fishbowl discussion strategycould gave the students motivation to speak freely and simply. It also made the students became more active, interested, enjoyable and fun in the class.